Technology and equipment for bioethanol producing from plant waste - Dmitry Prosvirnikov; Denis Tuntsev; Yuliya Kulikova; Olga Babich (Center of Biomass & Renewable Energy (CBIORE), 2026)
This study addresses the critical challenge of utilizing waste from agricultural industries by developing an efficient technology for its conversion into bioethanol. The research focuses on the application of steam explosion treatment as a pre-activation step for lignocellulose biomass, specifically pine wood and wheat straw. The novelty of the work lies in obtaining new fundamental data on the acid and enzymatic hydrolysis of steam-exploded materials and optimizing the subsequent biochemical conversion process to produce an alternative energy resource. The raw materials were subjected to steam explosion activation at saturated steam temperatures of 165 °C and 210 °C. Component analysis revealed that this pre-treatment effectively removes hemicelluloses and pentose sugars, which are not fermented by standard yeasts, while increasing the specific surface area and reactivity of the lignocellulose matrix. Acid hydrolysis of activated pine wood and enzymatic hydrolysis of activated wheat straw were investigated to produce hydrolysates rich in hexose monosaccharides. The results demonstrated that steam-explosive activation significantly enhances the hydrolysis rate and yield of reducing substances (RA). Activated pine wood was maximally converted to RA 1.7-2.5 times faster than untreated wood. In addition, activation at 210 °C allowed us to obtain hydrolysates with a minimum content of pentose, which in this study acted as inhibitors of the fermentation process. Subsequent anaerobic fermentation of these optimized hydrolysates using Saccharomyces cerevisiae achieved high ethanol yields. Specifically, steam-explosive activation of pine wood at 210 °C enabled the production of up to 0.26 kg (0.33 L) of ethanol per 1 kg of activated raw material, representing 36.7% of the RA. For wheat straw activated at the same temperature, enzymatic hydrolysis yielded up to 0.172 kg (0.218 L) of ethanol per 1 kg of activated straw. The study concludes that steam explosion is a highly effective pre-treatment method, facilitating the production of high-quality hydrolysates for efficient bioethanol production, thereby contributing to sustainable energy development and waste valorization.